A scoping review of environmental governance challenges in southern Africa from 2010 to 2020. (19th December 2021) - Falayi, Menelisi; Gambiza, James; Schoon, Michael
Summary: Throughout southern Africa, there have been growing concerns about the rates of ecosystem degradation. This issue and natural resource governance concerns in general remain key challenges. We conducted a scoping review of 135 articles to inductively assess how governance challenges have manifested in natural resource management during 2010–2020 in southern Africa. The paper's findings show that governance challenges in southern Africa are 'hydra-headed'. The results suggest that governance challenges related to the maintenance of system integrity and functioning – specifically lack of coordination, accountability, capacity, skills and resources to define effective natural resource management – were the most reported in literature. Challenges related to achieving socially equitable governance were the second most mentioned, followed by those related to institutional robustness. Challenges related to the adaptability and flexibility of institutions, specifically learning, monitoring capacity and innovation, were the least identified, showing that these areas are poorly studied or that these attributes are considered less problematic for achieving sustainable outcomes. Furthermore, the review highlights critical gaps – the limited engagement with governance-related frameworks, specifically polycentricity, adaptive governance and social-ecological stewardship. In concluding, we highlight governance reforms and future research needs on the topic of natural resources in southern Africa.